Revision and cladistic analysis of the Afrotropical endemic genus Smeringopus Simon, 1890 (Araneae: Pholcidae) - Huber, Bernhard A. (Zootaxa, 2012)
The genus Smeringopus Simon, 1890 is revised, with redescriptions of most previously known species and descriptionsof 36 new species. With now 55 species, Smeringopus becomes the most species-rich pholcid genus in Africa.Smeringopus is largely restricted to central, southern, and eastern Africa, where it includes some of the largest and mostconspicuous pholcid spiders in the region. A first cladistic analysis of Smeringopus, including outgroup representatives ofall other genera of Smeringopinae, strongly suggests that the central and western African Smeringopina Kraus, 1957 isthe sister taxon of Smeringopus. Smeringopus is here divided into twelve operational species groups, most of which arecharacterized by putative synapomorphies and by specific geographic distributions. Three species are newly synonymizedwith S. pallidus (Blackwall, 1858): S. excavatus (Simon, 1877); S. pholcicus Strand, 1907; and S. buehleri Schenkel, 1944.Smeringopus madagascariensis Millot, 1946 is newly synonymized with S. carli Lessert, 1915. Crossoprizacylindrogaster Simon, 1907 is transferred to Smeringopus. The following new species are described: S. badplaas; S. blyde;S. bujongolo; S. butare; S. bwindi; S. chibububo; S. chogoria; S. dehoop; S. dundo; S. florisbad; S. hanglip; S. harare; S.isangi; S. kalomo; S. katanga; S. koppies; S. lotzi; S. lubondai; S. luki; S. lydenberg; S. mayombe; S. mgahinga; S. mlilwane;S. moxico; S. mpanga; S. ndumo; S. ngangao; S. oromia; S. principe; S. ruhiza; S. saruanle; S. sederberg; S. tombua; S. turkana; S. ubicki; S. uisib.